Analisis Peran Penerangan Jalan Umum Tenaga Surya (PJU-TS) dalam Meningkatkan Visibilitas dan Keselamatan Transportasi pada Jalan Lintas Selatan (JLS) Lot 3 Blitar - Shofi Qurrota’ayun Azzahro; Devira Hernita Putri; Nugroho Utomo (Racic : Rab Construction Research, 2026)
Traffic safety at night is strongly influenced by the quality of road lighting, particularly on newly constructed roads with complex geometric characteristics. This study aims to analyze the effectiveness of solar-powered Public Street Lighting (PJU) in improving transportation safety on the Southern Cross Road (JLS) Lot 3 Blitar and to compare it with JLS Lot 7, which is not yet equipped with lighting facilities. The research adopts a qualitative approach through nighttime field observations, visual documentation, road geometry analysis, literature review, and data triangulation with Road Safety Audit (RSA) recommendations. The solar-powered lighting system evaluated is the Integrated Solar System Light (ISSL) 80 W, installed at critical locations such as Spiral–Circle–Spiral (S–C–S) curves, an 80 m bridge, and segments prone to dark spots. The results indicate that increasing the number of lighting units from 49 to 102 significantly enhances visibility, improves drivers’ perception of road geometry, and reduces the risk of single-vehicle and run-off-road accidents. Adequate lighting also contributes to improved psychological comfort for road users. Furthermore, the application of solar energy through the ISSL 80 W system supports energy efficiency and sustainable road infrastructure development